EALES DISEASE - Khan, Mohammad Naeem; Raza, Syed Shahmeer; Qadir, Shayan; Rehman, Hana; Hussain, Amer Kamal; Nadeem, Muhammad Daniyal; Ullah, Farhan (Journal of Ayub Medical College Abbottabad, 2016)
Eales disease is an eponym after a British ophthalmologist Henry Eales. The etiology behind Eales disease is ill-understood and stands controversial. Various systemic diseases associated with peripheral retinal revascularization and Retinal vasculitis could imitate the proliferative and inflammatory phases of Eales' disease, respectively. We present a case of a 30 years old female patient with Eales disease and discuss the clinical features, treatment plan and its outcome in our patient. Tuberculosis appears to be the cause of Eales disease but the relation is yet to be established and clinically proven. Steroid therapy is usually the main stay of treatment with tapering doses of systemic corticosteroids. Other interventions are vitrectomy, photocogulation or cryotherapy. Keywords: Eales disease; Tuberculosis; Fundus Fluorescein Angiography; Retinal Vasculitis